Motor Competence and Attainment of Global Physical Activity Guidelines among a Statewide Sample of Preschoolers - Slaton, Anthony (Int J Environ Res Public Health, 2020)
Global physical activity guidelines for preschoolers include 60 min of moderate-to-vigorous physical activity (MVPA) daily. This study, based on the developmental model of motor skill competence, examines how motor competence relates to preschoolers’ likelihood of meeting global guidelines using ankle accelerometry. We measured physical activity using 24-h ankle-placement accelerometry (Actical) for at least two consecutive days (87% with six-seven days), motor competence using the Test of Gross Motor Development-2 (TGMD-2), and BMI-for-age z-scores (BMIz) using anthropometry and age- and sex-specific CDC norms. Caregivers provided demographic characteristics of children’s age, sex, and race. We used multivariable logistic regression to examine how motor competence, BMIz weight status, and demographic characteristics related to meeting global physical activity guidelines. The sample included 588 preschoolers, age 3–5 years; 55% male; 60% white; and 28% overweight/obese; 75% attained the recommended 60 min of MVPA per day. The odds of meeting MVPA guidelines were associated with higher gross motor quotient, higher object control scores, sex (male), age (older), and race (white), but not with BMIz weight status. Findings support the use of 24-h ankle accelerometry among preschoolers and are consistent with the developmental model of motor competence applied to preschoolers, whereby object control competence relates positively to attaining global physical activity guidelines.